Improving Depth Perception with Motion Parallax and Its Application in Teleconferencing - Zhang, Cha; Yin, Zhaozheng; Florencio, Dinei (MMSP'09, 2009)
Depth perception, or 3D perception, can add a lot to the feeling of immersiveness in many applications such as 3D TV, 3D teleconferencing, etc. Stereopsis and motion parallax are two of the most important cues for depth perception. Most of the 3D displays today rely on stereopsis to create 3D perception. In this paper, we propose to improve user’s depth perception by tracking their motions and creating motion parallax for the rendered image, which can be done even with legacy displays. Two enabling technologies, face tracking and foreground/background segmentation, are discussed in detail. In particular, we propose an efficient and robust feature based face tracking algorithm that is capable of estimating the face’s location and scale accurately. We also propose a novel foreground/background segmentation and matting algorithm with time-of-flight camera, which is robust to moving background, lighting variations, moving camera, etc. We demonstrate the application of the above technologies in teleconferencing on legacy displays to create pseudo-3D effects.